2013
DOI: 10.5028/jatm.v5i2.193
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on Thermal Properties of PEI/Glass Fiber Composite Materials

Abstract: The aim of this study was to investigate the effects of hygrothermal exposure, ultraviolet (UV) radiation, salt spray and thermal shock aging on the thermomechanical behavior of glass fiber reinforced by poly (ether-imide) (PEI) composites. Dynamic mechanical (DMA) and Thermomechanical (TMA) analyses have been performed on the aged PEI composites after being submitted to the climatic chambers. Additional techniques have been used to characterize the laminates, such as optical microscopy and infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The material responses of FRP composite structures subjected to different environmental effects have been well-reported [143,144,[148][149][150][151][152][153][154][155][156]. Ray [148] observed that by changing the humidity cycle, the moisture absorption rate changes with a constant temperature environment, and also depends on the sort of matrix resin as well as the weight ratio of ingredients.…”
Section: Environmental Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The material responses of FRP composite structures subjected to different environmental effects have been well-reported [143,144,[148][149][150][151][152][153][154][155][156]. Ray [148] observed that by changing the humidity cycle, the moisture absorption rate changes with a constant temperature environment, and also depends on the sort of matrix resin as well as the weight ratio of ingredients.…”
Section: Environmental Propertiesmentioning
confidence: 92%
“…The environmental effects (ultraviolet radiation, hygrothermal exposure, thermal shock aging and salt spray) on the thermal properties of glass fiber (GF) reinforced by poly (ether-imide) (PEI) composites were investigated by Botelho et al [151]. The experiment was carried out with diverse temperatures at corresponding moisture of 90% for 60 days beneath seawater.…”
Section: Environmental Propertiesmentioning
confidence: 99%
“…Botelho et al. 60 investigated the environmental behaviour of woven mat GF-reinforced poly ether-imide thermoplastic matrix composites. The testing was conducted with varying temperature at relative humidity of 90% for 60 days under sea water.…”
Section: Environmental Behaviours Of Gfrp Matrix Compositesmentioning
confidence: 99%
“…The absorption of water molecules present in the crude oil/water system into the macromolecular network of a thermoplastic has not been investigated comprehensively especially when it is combined with harsh environmental conditions such as elevated temperature and ultraviolet radiation [1]. The combined effect of temperature, humidity and ultraviolet radiation on the properties of polyester and/or glassfiber composite materials has been investigated using an environmental accelerated aging chamber [2]. Thereby, similar studies are desired in this area as the use of composite products and composite pipes is surging in the oil sector.…”
Section: Introductionmentioning
confidence: 99%